Design of irregular concatenated zigzag codes - Song-Nam Hong; Dong-Joon Shin (Proceedings / IEEE International Symposium on Information Theory, 2005)
Capacity-approaching codes using iterative decoding have been the main research subject of coding area during past decade. In this paper, a new channel coding scheme called irregular concatenated zigzag (ICZZ) code is proposed. ICZZ codes can be viewed as a special case of irregular low-density parity-check (LDPC) codes with linear-time encodable structure. They are different from concatenated zigzag (CZZ) codes in the sense that the number of information bits entering into each zigzag encoder can be different and different zigzag codes can be used as component codes. A simple method to design ICZZ codes is proposed and by using an example, it is shown that ICZZ code of rate 1/3 has better performance than the optimal CZZ code and turbo code adopted in 3GPP